2014
DOI: 10.1007/s12035-014-8940-1
|View full text |Cite|
|
Sign up to set email alerts
|

Inhibitory Effects of Bisphenol-A on Neural Stem Cells Proliferation and Differentiation in the Rat Brain Are Dependent on Wnt/β-Catenin Pathway

Abstract: Neurogenesis, a process of generation of new neurons, occurs throughout the life in the hippocampus and sub-ventricular zone (SVZ). Bisphenol-A (BPA), an endocrine disrupter used as surface coating for packaged food cans, injures the developing and adult brain. However, the effects of BPA on neurogenesis and underlying cellular and molecular mechanism(s) are still unknown. Herein, we studied the effect(s) of prenatal and early postnatal exposure of low dose BPA on Wnt/β-catenin signaling pathway that controls … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
77
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 98 publications
(83 citation statements)
references
References 121 publications
6
77
0
Order By: Relevance
“…previous studies demonstrated that BPA exposure inhibits NSC proliferation and differentiation and also causes neurodegeneration in the hippocampus (1)(2)(3). In the present study, we found increased mitochondrial fission, increased oxidative stress, and apoptosis.…”
Section: Bpa-mediated Increased Apoptosis and Inhibition Of Nsc Prolisupporting
confidence: 76%
See 4 more Smart Citations
“…previous studies demonstrated that BPA exposure inhibits NSC proliferation and differentiation and also causes neurodegeneration in the hippocampus (1)(2)(3). In the present study, we found increased mitochondrial fission, increased oxidative stress, and apoptosis.…”
Section: Bpa-mediated Increased Apoptosis and Inhibition Of Nsc Prolisupporting
confidence: 76%
“…Hippocampal NSC Culture-Hippocampus-derived NSC culture was carried out following our previous studies (2,3,62). Briefly, pregnant Wistar rats were deeply anesthetized with a mixture of ketamine and xylazine (3:1 ratio) and dissected cautiously to remove the embryos at embryonic day 12.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations